Pengaruh Model Pembelajaran E-Learning Terhadap Hasil Belajar IPA Siswa Kelas IV SDN Se-Kecamatan Alian Tahun Ajaran 2021/2022 - Vena Nur Litasari; Muhamad Chamdani; Tri Saptuti Susiani (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2022)
AbstractThe study aimed to prove the effect of e-learning on natural science learning outcomes to fourth grade students of public elementary schools in Alian Sub-district in academic year of 2021/2022 and to measure the contribution of e-learning on natural science learning outcomes to fourth grade students of public elementary schools in Alian Sub-district in academic year of 2021/2022.The population were 762 fourth grade students and the samples were 264 fourth grade students. Data collection techniques used questionnaires and tests. The validity method included question analysis using Pearson correlation analysis. Reliability used the Alpha (Cronbach’s) formula. The prerequisite test used linearity and normality tests. Data Analysis used simple regression analysis, simple correlation, and adjusted R square with a significance level of 5%.The results showed that the correlation value of e-learning was 0.342 on science learning outcomes. The significance value was 0,000less than 0.05. The e-learning contributed 69.9% on natural science learning outcomes and the remaining 30.1% was influenced by other factors.